Open source and new media artists - Halonen, Katri (Human Technology, 2007)
This paper deals with the open source method practiced within the new media art context. I present a case study on an international festival, PixelACHE 2005, which was organized by and for new media artists and served as a platform for demonstrations of new media projects and as a meeting place for experimental new media artists. In this article I discuss how new media artists adapted the open source ideology. Open source is seen both as a more liberal method of distribution and as an open joint creative process. I was particularly interested in what kind of motives the new media artists had for taking part in the PixelACHE festival and the joint artistic creative process. In my analysis, I found four different groups that have diverse motives for participating in open source art projects. One group contains the key persons who use the open source network as an important reference in their professional image. Members of the second and third group are new media artists who earn their main income in either the public or corporate sector and use open source projects as a learning platform. The fourth group comprises young enthusiasts who are seeking jobs and professional networking opportunities in the open source network.